Alvarado score and computerized tomography scan as impact indicator in intervening negative appendectomy rate - Mishra, Braja Mohan; Panigrahi, Pramit Ballav; Mishra, Sandeep; Mohapatra, Abinasha (International Surgery Journal, 2020)
Background: The objective of this study is to study the impact of combined use of Alvarado score and computed tomography (CT) scan on negative appendectomy rate. Methods: This prospective observational study comprising of patients presenting with clinical features of appendicitis admitted to department of general surgery, VIMSAR, Burla from November 2017 to October 2019, where Alvarado score and ultrasonography (USG) findings are mismatching each other. Alvarado scores calculated and categorized in 2 groups as negative (score <4) and positive (score ≥4). These patients were also subjected to USG and categorized as negative (USG -ve) and positive (USG +ve). Those patients having discrepancy in both the findings were subjected to CT scan. On histopathological examination, inflamed appendix in 63 (97%) patients and non-inflamed in 2 (3%). Rest patients were either discharged (both -ve) or operated (both +ve). Results: Total 84 patients showed discrepancy between Alvarado score and USG findings and are subjected to CT scan abdomen and pelvis. CT scan was positive for appendicitis in 65 cases (where appendectomy done) and negative for appendicitis in 19 cases (where the diagnosis is different). patient. Thus, negative appendectomy (NAR) is 3% in this study. Conclusions: Alvarado score and ultrasonography could not be used as absolute tool in doubtful and equivocal cases, where combined use of CT scan with Alvarado score and USG has definitely has an edge by diagnosing the differentials and reducing NAR followed by reduction in cost and length of hospital stay.